SISTEM DESIGN OF FAULT TOLERANCE PROTOTYPE DOOR CONTROLLER BASED SYSTEM PERSONAL COMPUTER - Martian Logi Otama; Drs. Lingga Hermanto, MMSI (Jurnal Sistem Komputer, 2006)
Fault tolerance describes a computer system designed to handle the event when the system experienced an error (fault) the work, which the backup or replacement procedures will replace the work experience component failures without interrupting the continuity of the systemIn this tool will be designed with fault tolerance system implemented on the controller door through techniques passcode Microsoft Access 2000 database.The system is designed so that a procedure will be run on a PC to detect failures in the activation of work and continued with a replacement system (redundant) that is executed through a program based on Microsoft Visual Basic 6.0. Execution of the bridge through 8255 PPI interface.